(untitled) (Journal of Computational Mathematics, 2019)
Solving the advection-diffusion equation in irregular geometries is of great importance for realistic simulations. To this end, we adopt multi-patch parameterizations to describe irregular geometries. Different from the classical multi-patch parameterization method, C^1-continuity is introduced in order to avoid designing interface conditions between adjacent patches. However, singularities of parameterizations can't always be avoided. Thus, in this paper, a finite volume method is proposed based on smooth multi-patch singular parameterizations. It is called a singular parameterized finite volume method. Firstly, we present a numerical scheme for pure advection equation and pure diffusion equation respectively. Secondly, numerical stability results in L^2 norm show that the numerical method is not suffered from the singularities. Thirdly, the numerical method has second order accurate in L^2 norm. Finally, three numerical tests in different irregular geometries are presented to show efficiency of this numerical method.